Measurement and analysis of conductor surface temperature in dependence of current variation - Ali Hlal Mutlaq; Mahmood Ali Ahmed; Diadeen Ali Hameed; Ghanim Thiab Hasan (Bulletin of Electrical Engineering and Informatics, 2022)
The reliability and service life of power cables is closely related to the cable ampacity and temperature rise in the power cable. In a conductor carries AC current, complex processes may appear, which directly affect the temperature of the conductor surface. So, to keep a conductor in a good state, it is necessary to maintain the conductor temperature in a acceptable value. In this paper, a procedure for measuring the temperature of conductor surface and the corresponding numerical processing of measurement results has been presented. The measurement of the temperature probe characteristics and the temperature measurement on the surface of the conductor, both required the use of certain numerical methods, such as interpolation and fitting of the measured values in time diagrams. The procedure was applied to three copper conductors with different cross section area and one aluminum conductor and the final results are presented graphically, in the form of time diagrams.